Jovens geração Z : percepções na construção de um caminho em direção ao mundo do trabalho - Graebin, Rosani Elisabete (My University, 2018)
Research carried out by the Brazilian Youth Agenda (SNJ, 2014) portrayed the insertion in the world of work as one of the most relevant themes for young people's lives. The main objective of this study was to evaluate the positioning of young people in the 3rd year of high school in relation to the world of work, establishing a relationship with the perception of teachers and managers of human resources in Caxias do Sul. Aspects as the profile of the young person, meaning work, career, employability and technology were topics of discussion in this study. For this, as well as methodological aspects, an applied research of exploratory nature was adopted from a quantitative-qualitative study. The quantitative stage, operationalized through a survey, included students and teachers from public and private schools in Caxias do Sul. In the qualitative stage, in-depth interviews were conducted with human resources managers linked to companies in the metalworking sector of Caxias do Sul, with the objective of presenting the corporate perception about the insertion of young people in the world of work. Data were triangulated to provide a better understanding of the findings. Results indicated that the youngsters of the 3rd year of high school in Caxias do Sul have characteristics of Generation Z and that assigns a meaning to work from the choice of a profession that they consider important, for which they are interested and in which they feel happy, where success would be related to the adoption of good work habits. So he could give his best and be recognized as competent. Thus, in order to make the best career choices, the research pointed out that they should consider professions that meet their tastes, attitudes and qualities, analyzing their abilities, interests and values. Workability emerged as an evolution of the concept of employability, where the young person would develop the ability to work and generate income, offering the world of work something that he knows how to do well, in a more autonomous way, without the concern of being tied to a company formal employment regimes. From the workability, it can be inferred that the purpose is what establishes the relationships of the young generation Z with the aspects related to the work, that is, it needs to visualize a purpose in the work that will develop, otherwise it can easily become discouraged and seek new paths in search of goals and challenges.
Pesquisa realizada pela Agenda Juventude Brasil (SNJ, 2014) retratou ser a inserção no mundo do trabalho um dos temas mais relevantes para a vida dos jovens. O objetivo central desse estudo foi avaliar o posicionamento dos jovens do 3º ano do ensino médio em relação ao mundo do trabalho, estabelecendo uma relação com a percepção dos professores e gestores de recursos humanos de Caxias do Sul. Aspectos como o perfil do jovem, significado do trabalho, carreira, empregabilidade e tecnologia foram temas de discussão nesse estudo. Para tanto, quanto aos aspectos metodológicos, adotou-se uma pesquisa aplicada de caráter exploratória a partir de um estudo quanti-qualitativo. A etapa quantitativa, operacionalizada por meio de uma survey, contemplou os alunos e professores das escolas públicas e particulares de Caxias do Sul. Na etapa qualitativa foram realizadas entrevistas em profundidade com gestores de recursos humanos ligados a empresas do setor metalmecânico de Caxias do Sul, com o objetivo de apresentar a percepção empresarial sobre a inserção do jovem no mundo do trabalho. Realizou-se uma triangulação dos dados a fim de propiciar uma melhor compreensão a respeito dos achados. Resultados apontaram que o jovem do 3º ano do ensino médio de Caxias do Sul tem características da Geração Z e que atribui um significado ao trabalho a partir da escolha de uma profissão a qual considere importante, pela qual se interesse e na qual se sinta feliz, onde o sucesso estaria relacionado à adoção de bons hábitos de trabalho. Assim, ele poderia dar o seu melhor e ser reconhecido como competente. Com isso, a fim de realizar as melhores escolhas na carreira, a pesquisa apontou que eles deveriam considerar profissões que fossem ao encontro dos seus gostos, suas atitudes e qualidades, analisando suas capacidades, interesses e valores. A trabalhabilidade surgiu como uma evolução do conceito de empregabilidade, onde o jovem desenvolveria a habilidade de trabalhar e gerar renda, oferecendo ao mundo do trabalho algo que ele saiba fazer bem, de uma forma mais autônoma, sem a preocupação de estar vinculado a uma empresa pelos regimes formais de emprego. A partir da trabalhabilidade, pode-se inferir que o propósito é o que estabelece as relações do jovem geração Z com os aspectos relacionados ao trabalho, ou seja, ele precisa visualizar um propósito no trabalho que irá desenvolver, caso contrário, pode facilmente se desmotivar e buscar novos caminhos à procura de propósitos e desafios.
Keywords: Jovens - Emprego; Mercado de trabalho; Orientação profissional; Tecnologia; Youth - Employment; Labor market; Vocational guidance; Technology